Learning to Teach by Practice: Pre-service Teachers’ Experiences of Using Poetry Memorization, Dramatization and Recitation Pedagogy - Nambi, Rebecca; Busimba, James Taabu; Lutaaya, Josephine Najjemba; Atuhura, Dorothy; Nabiryo, Nancy Rosemary (Advances in Social Sciences Research Journal, 2024)
In Uganda, poetry is a key genre in the Literature in English curriculum at the secondary and higher institutions of teacher education. However, many teachers, especially the novices, struggle with the teaching of poetry in secondary schools in Uganda. Current approaches to teaching support learner-centered pedagogy where learners are facilitated to fully participate in scaffolding their own interpretations of the subject content. Individual in-class poetry recitation is one such activity used to teach, and taught to, pre-service teachers of poetry because it promotes their participation and their general attitude towards poetry. In this paper, we present findings from a study about Makerere University pre-service teachers’ experiences of using individual in-class poetry recitations as a learner-centered strategy for teaching poetry. The research was carried out amongst one cohort of finalist teacher trainees of English and Literature using lecture observation, interviews and open-ended questionnaire research methods. A thematic analysis of the data revealed three themes that summarize their experiences with memorization, recitation and dramatization of poetry: recitation: facing the class; and pedagogical reflections. As we present these themes, we also draw some pedagogical implications for poetry classes from the actual recitation experiences of teacher trainees who participated in this study.